Chicoreus brunneus seashells as a catalyst in rice bran biodiesel production / Hoora Mazaheri - Hoora , Mazaheri (2020)
Environmental pollution and the declining global supply of accessible fossil fuels are the key drivers to search for alternative energy sources. This study focused on developing a “green” and sustainable heterogenous calcium oxide (CaO) catalyst from Chicoreus Brunneus shells for biodiesel production from rice bran oil (RBO). Coastal people frequently collect these shells for food and shell crafts. Thus, by using seashell wastes, cost-efficient catalysts can be achieved for the biodiesel industry. The shells were calcinated, washed and dried to produce pure CaO catalyst. After that, CaO was converted into calcium methoxide (Ca(OCH3)2) and followed by loading onto zeolite support with wet impregnation to produce the hybrid catalyst. Both pure and hybrid catalysts along with methanol were used for the transesterification of RBO. The properties of the biodiesel were further evaluated. The tribological characteristics of biodiesel were assessed. Analytical tools have determined the formation of catalysts from C. brunneus. The surface of Ca(OCH3)2 increased to 84.67 from 3.30 m²/g upon impregnation with zeolite. BET properties, average pore diameter and pore size of C. brunneus shell were also greater than that of commercial CaO catalyst. Both catalysts manifested relatively appreciable stability during the transesterification reaction with pure and hybrid catalysts presented the FAME yield of 93 and 98% respectively. However, FAME yield decreased significantly after the fifth transesterification reaction, and this was coincident with changes in the surface morphology of the catalysts. The fuel properties of biodiesel were within the ASTM D6751 and EN 14214 standards for biodiesel. The acid value of the biodiesel using the hybrid catalyst was 0.29 mg KOH, which was lower than the acid value obtained by the pure catalyst (0.5 mg KOH). The tribological examination suggested that 10% of biodiesel known as RBOB10 has a significant capacity as a mineral lubricant due to presenting the least wear scar diameter (462.3 μm) and lowest friction coefficient (0.085). From the results, the C. brunneus catalyst has the potential to be applied as industrial CaO nanocatalyst due to its large surface area and high stability which could increase the total yield of FAME. From the economic aspect, it is possible to recover C. brunneus derived catalysts in a facile way and to reuse them up to five cycles. They can be used frequently in the production cycles with constant catalytic activity and can potentially reduce the capital production cost. Further, the use of these catalysts simplifies the purification process, leading to reduced energy consumption and waste minimization. Overall, an efficient Ca(OCH3)2 catalyst was developed from a novel type of seashell, i.e., C. brunneus which showed to be a prominent catalyst over the other sources of Ca(OCH3)2. Moreover, the produced catalyst resulted in a FAME yield of 98% within 120 min, having a higher yield in reduced reaction time, comparing with other synthetic catalysts. Therefore, the capacity of C. brunneus shell based-Ca(OCH3)2 as a potential renewable source of CaO-based nanocatalyst for biodiesel production has been studied and approved.